Preferensi Konsumen Dalam Membeli Gula Aren Di Pasar Bersehati Kota Manado - Monolimay, Frelly; Lolowang, Tommy Ferdy; Talumingan, Celcius (AGRI-SOSIOEKONOMI, 2024)
This study aims to determine consumer preferences in buying palm sugar at Bersehati Market, Manado City, which is very important for palm sugar sellers in order to have the opportunity to earn more income or profit. This research was conducted for 2 months from February to March 2023. The research took place at Bersehati Market, Manado City. Data collection used observation and interview methods. Sampling in this study was non-probability, namely convenience sampling to consumers of palm sugar at Bersehati Market which was taken as many as 30 respondents. Data on consumer preferences in buying palm sugar in Bersehati Market were analyzed descriptively with the help of tables. The results showed that the palm sugar that became consumer preferences in making purchasing decisions was palm sugar that had a blackish brown color, retail cut size, plastic packaging with a price that was not too expensive, namely IDR 8.000 to IDR 20.000.